2004
DOI: 10.1111/j.1096-3642.2003.00101.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic position of and generic distinction between Parepactophanes Kunz, 1935 and Taurocletodes Kunz, 1975 (Copepoda, Canthocamptidae incertae sedis), with description of a new species from the Black Sea

Abstract: Both sexes of a new species of Taurocletodes Kunz, 1975 (Copepoda, Harpacticoida, Canthocamptidae incertae sedis ) are described from sandy beaches along the Black Sea coast of Turkey. The genus Taurocletodes is removed from its synonymy with Parepactophanes Kunz, 1935 and re-instated as a valid genus, accommodating the type species T. dubius (Noodt, 1958) comb. nov. and T. tumenae sp. nov. Both genera can be differentiated by major differences in the segmentation of P1-P3 endopods, the absence/presence of pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 430 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Examination of a number of genera revealed that the pore is present in Canthocamptus staphylinus (Jurine, 1820), but absent in Mesochra Boeck, and a wide range of freshwater genera such as Elaphoidella Chappuis, Attheyella Chappuis, and Moraria T. & A. Scott. It is also absent in brackish‐water representatives of Cletocamptus Shmankevich (Gee, 1999) and a number of marine genera excluded from the Cletodidae and attributed to the Canthocamptidae by Por (1986): Parepactophanes Kunz, Taurocletodes Kunz, Heteropsyllus T. Scott, and Hemimesochra Sars (Karaytuğ & Huys, 2004; R. Huys, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of a number of genera revealed that the pore is present in Canthocamptus staphylinus (Jurine, 1820), but absent in Mesochra Boeck, and a wide range of freshwater genera such as Elaphoidella Chappuis, Attheyella Chappuis, and Moraria T. & A. Scott. It is also absent in brackish‐water representatives of Cletocamptus Shmankevich (Gee, 1999) and a number of marine genera excluded from the Cletodidae and attributed to the Canthocamptidae by Por (1986): Parepactophanes Kunz, Taurocletodes Kunz, Heteropsyllus T. Scott, and Hemimesochra Sars (Karaytuğ & Huys, 2004; R. Huys, pers. observ.).…”
Section: Discussionmentioning
confidence: 99%
“…This state of affairs has inspired other people to include even more marine genera in this family and, in one instance, an entire subfamily was transferred (Por, 1986). The Canthocamptidae, once a morphologically homogeneous, primarily freshwater‐inhabiting family, currently contains 55 genera, 18 of which are found in fully marine or estuarine habitats (Boxshall & Halsey, 2004; Karanovic, 2004; Karaytuğ & Huys, 2004). Paradoxically, subsuming the Cylindropsyllidae within this family would increase this number to 27, half of the total number of genera.…”
Section: Systematicsmentioning
confidence: 99%
“…The find of this material prompted us to analyze and reconsider the taxonomic position of the genus. The taxonomic history of the Canthocamptidae is very complex, and the main approach to understand the relationships amongst its constituent genera has been the proposal of several subfamilies and species groups, e.g., the Rhyncoceratinae Labbé, 1926, the Biarticulata and the Uniarticulata (Chappuis 1929a), the Canthocamptinae Brady, 1880, the Halocanthocamptinae Pesta, 1932, the six species groups of Gurney (1932), the Morariinae Borutzky, 1952, the Epactophaninae Borutzky, 1952, and more recently the Mesochra group sensu Karaytuğ and Huys (2004), but it seems none of these subfamilies/groups are natural units. In this study, we propose a new subfamily, the Cletocamptinae subfam.…”
Section: Introductionmentioning
confidence: 99%
“… Karaytuğ and Huys (2004) recognized within the primarily freshwater Canthocamptidae a core complex of genera confined to marine and brackish water habitats which they called the Mesochra -group. This group, which is fundamentally different from Por’s (1986) taxonomic concept of the Hemimesochrinae , comprises the genera Mesochra Boeck, 1865, Parepactophanes Kunz, 1935, Mesopsyllus , Psammocamptus Mielke, 1975, Taurocletodes Kunz, 1975, Amphibiperita Fiers & Rutledge, 1990, Bathycamptus Huys & Thistle, 1989, and Isthmiocaris George & Schminke, 2003.…”
Section: Introductionmentioning
confidence: 99%